Pengembangan Buku Pendidikan Karakter Rasa Ingin Tahu Dengan Permainan Tradisional Untuk Anak Usia 7–9 Tahun - Amanda, Rosalia; Amanda Utami, Rosalia (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2024)
The character education of curiosity is increasingly being eroded due to limited facilities which have an impact on the emergence of serious problems. The aim of this research is to develop a guidebook for traditional games that can improve the curious character of children aged 7-9 years. The research method used is Research and Development (R&D) with the ADDIE approach. This research involved ten certified teachers as respondents to the needs analysis. Apart from that, four lecturers, four certified teachers, traditional game practitioners and artists are also involved as validators of traditional game book products. The subjects involved in this limited research trial were eight children aged 7-9 years. Based on this research, it can be summarized in three main points, namely 1) The product was developed through the ADDIE stages, 2) The quality of the research product obtained an average score of 3.84 and met the criteria